Effects of Iodine Treatment on the Development of Eggs and Larvae of Rabbitfish (Siganus guttatus Bloch, 1787) - Huyen Kieu Thi; Vinh Phuong Tran; Nguyen Ngoc Tran; Thi Huong Giang Ngo; Ngoc Tram Anh Ho; Xuan Huy Nguyen; Quang Linh Nguyen (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract